Amalan Pengiraan Pendapatan Kasar bagi Projek Perumahan Kos Sederhana Rendah - Abdullah, Anis Nabila; Zainal, Rozlin; Kasim, Narimah; Abdul Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2022)
The calculation of the gross income of a housing project is the price of the development to be carried out. Yet the problem of inaccurate use of methods and information by developers can affect the decision-making process on planning especially for low -medium cost housing projects. Therefore, the objective of this study is to identify the methods used by developers when calculating gross income for low medium cost housing projects, identify information often used by developers when calculating income. The scope of this study involves housing developers in the Johor area. This study uses a quantitative approach through the distribution of questionnaires to respondents, namely 150 developers of low -medium housing projects in Johor and the data analysis used is descriptive statistical analysis that is frequency analysis, mean and crosstabs. The results of the study found that the methods that are often used are financial analysis method, SWOT analysis method, brainstorming method and ratio analysis method in addition to the information that is often used is house price, development cost and project duration. Therefore, this study can help housing developers make decisions when calculating gross income or initial income for a housing project and make developers aware that information is an important element that can be used as a guideline to calculate gross income of the project more accurately.